How do student loans impact the American Dream? Exploring the implications of federal, private and parent PLUS student loan debt on homeownership - Usrey, Wendy Adele (Kansas State University, 2023)
The importance of homeownership for individuals and society is well documented in the literature. Real estate plays a significant role in the portfolios of households and as the largest single component of U.S. GDP, the strength of the nation’s economy, and others across the globe, are heavily affected by the health of U.S. real estate markets(Yun, 2015, 2016; Yun et al., 2022; Yun & Evangelou, 2016). Despite its importance, homeownership rates in the U.S. have been declining since the 1980’s, particularly among younger households, and there is a growing body of evidence suggesting that student loans are a significant obstacle to home purchases (Glassman et al., 2019; National Association of Realtors, 2021; National Association of Realtors Research Division & American Student Assistance, 2017; Prudential Research & Perspectives, 2019) Federal student loans are the most common type of student loan and offer the most flexible and affordable payment options. However they are subject to borrowing limits, which have not kept pace with the cost of tuition, forcing many borrowers and their families to turn to less flexible and more expensive parent PLUS and private loans to finance higher education expenses. Total outstanding student loan debt topped $1.75 trillion by the third quarter of 2022, with private student and PLUS loans accounting for roughly 7.24 and 5.5% of the total, respectively (Board of Governors of the Federal Reserve, 2023; Enterval Analytics, 2023). (Fletcher & Webster, 2020; Kreighbaum, 2019). Unlike other forms of consumer debt, student loans are rarely dischargeable in bankruptcy and the penalties for default are particularly harsh. Recent economic indicators including rising interest rates, wavering consumer confidence, and stagnant real wages, point to early signs of weakening housing markets. Given its importance in the overall health of the nation’s economy, these trends are of particular concern. Furthermore, the recent resumption of federal student loan payments after more than 3 years of deferment during the COVID-19 pandemic is already raising concerns among experts for the impact they will have on consumer budgets and their ability to qualify for a mortgage, adding particular urgency and relevance to this research (Colomer, 2023; Sheffey, 2023; Sor, 2023). While previous research has generally shown that student loans have a negative impact on homeownership, most of the relevant literature has only measured the effects the presence student loan debt has on homeownership rather than considering the size or type of the debt in the analyses. Because debt payments, rather than total outstanding debt are a central factor in mortgage underwriting decisions, including student debt payments is essential for thorough analysis of housing tenure decisions. By shedding light on the relationships between various types of student loans, homeownership, and borrowing behavior this study fills an important gap in the literature as it relates to types of student loan debt, homeownership, and mortgages. Following the neoclassical theory of housing demand, this research utilizes the 2019 Survey of Consumer Finances to examine these relationships with four different models. First, a logistic regression model was used to assess the impact of student loans on homeownership, next a selection model was developed to analyze the impact between student loans and a household’s mortgage debt burden. Finally, the relationships between student loans and mortgage types, specifically, adjustable-rate and federally insured/guaranteed mortgages, were examined. Results confirm previous findings that student loans generally reduce the likelihood of homeownership, increase mortgage burdens, and lead borrowers towards riskier or costlier mortgage options. Importantly, this research also unveils new insights regarding the impact of different types of student loans on homeownership. Federal loan holders, for instance, are less likely to own a home than households without student loan debt but have a higher likelihood of homeownership compared to borrowers with private or parent PLUS student loans. The research also shows that the amount of student loan debt is a significant factor affecting homeownership, with various types of loans having different effects. Further, results indicate student loan payment burdens affect the monthly cost of a mortgage as well as the type of mortgage a borrower qualifies for, differing across student loan types and independent of other household characteristics. Student loan borrowers are more likely to secure adjustable-rate and federally backed mortgages in general, with federal loan borrowers having a higher probability of holding a federally backed mortgage than private loan holders, who in turn had a higher probability of holding a federally backed mortgage than parent PLUS loan borrowers. Having private loans also increases the probability of having an adjustable-rate mortgage, while increasing private and parent PLUS loan balances and payment burdens also increase the probability of having an adjustable-rate mortgage. In summary, this research offers compelling evidence that student loans overall, student loan payment burden, as well as the type of student loan held, play substantial roles in shaping homeownership outcomes for student borrowers with existing loans (results may not accurately capture the outcomes of those that previously borrowed but no longer have student loan debt). These findings contribute to a deeper understanding of the dynamics between student loans, homeownership, and mortgage choices, shedding light on critical factors that influence housing tenure decisions.
Keywords: Student loans; Homeownership; Private student loans; Federal student loans; Parent PLUS student loans; Mortgages